2011
DOI: 10.3349/ymj.2011.52.6.982
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Heat and Massage Application on Autonomic Nervous System

Abstract: PurposeThe objective of this study is to evaluate the effects of heat and massage application on autonomic nervous system.Materials and MethodsOne hundred thirty-nine subjects volunteered and completed this study. Heat and massage was daily applied for 40 minutes, 5 days a week for 2 weeks. Primary-dependent measures included heart rate variability, sympathetic skin response, and serum cortisol and norepinephrine levels.ResultsSerum cortisol levels were significantly decreased at 2 weeks compared to baseline (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 28 publications
5
42
0
2
Order By: Relevance
“…Previous research reported a decrease in sympathetic activity with heat and massage application over time, as well as a decrease in LF/HF ratio in preterm infants undergoing massage compared to controls; however, none of these results were following an exercise session, and the massage with heat application utilized mechanical massage techniques as opposed to manual techniques. (3,17) Results comparing cool-down exercise to recovery from exercise without cool-down exercise suggested that cool-down is associated with increased HF amplitude and is closely related to the decline in the mean level of HR during recovery from exercise. (18) In this case study, a decrease in mean HR with massage recovery above and beyond that which occurred with resting recovery was observed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research reported a decrease in sympathetic activity with heat and massage application over time, as well as a decrease in LF/HF ratio in preterm infants undergoing massage compared to controls; however, none of these results were following an exercise session, and the massage with heat application utilized mechanical massage techniques as opposed to manual techniques. (3,17) Results comparing cool-down exercise to recovery from exercise without cool-down exercise suggested that cool-down is associated with increased HF amplitude and is closely related to the decline in the mean level of HR during recovery from exercise. (18) In this case study, a decrease in mean HR with massage recovery above and beyond that which occurred with resting recovery was observed.…”
Section: Methodsmentioning
confidence: 99%
“…(1) Massage, a mechanical manipulation of body tissues with rhythmical pressure and stroking, is often used to promote health and well-being, with the benefit of increasing parasympathetic activity and decreasing sympathetic activity in a rested state, indicating a reduced stress response. (2,3) The manual manipulation of massage is associated with increased parasympathetic activity, which indicates an improved level of homeostasis. (4) While there are no well-established techniques for evaluating parasympathetic activity, heart rate variability (HRV), the ability of the heart to modulate in response to the fine control of the parasympathetic nervous system, is often used to reflect the influence of the autonomic nervous system (ANS) on heart rate.…”
Section: Comparing the Effects Of Rest And Massage On Return To Homeomentioning
confidence: 99%
“…While specific studies on this specialized form of neuromuscular therapy are forthcoming, existing research on massage therapy in general is informative. One study applied massage therapy to 139 volunteers for 40 min per day, 5 days per week for 2 weeks and measured HRV, sympathetic skin response and serum cortisol and norepinephrine levels before and after the treatment [104]. They found that serum cortisol levels and norepinephrine were significantly decreased, HRV increased and the sympathetic skin response latencies increased, all indications of a reduced sympathetic outflow.…”
Section: Re-regulation Of Ans and CDmentioning
confidence: 99%
“…Also, the massage pressure and location can be controlled precisely depending on the subjects' physical condition. Third, the automated massage can easily be combined with thermotherapy, where recent studies have suggested that massage accompanied with skin heating may have positive effects, such as increased skin blood flow [27] and decreased plasma cortisol and norepinephrine [28]. …”
Section: Introductionmentioning
confidence: 99%